Physical and sports activities adapted for autistic children in para-pedagogical centers between the opinions of specialists and popular beliefs (a field study of para-pedagogical centers for autistic children in Biskra - Hamdaoui, sofiane (sports creativity, 2024)
This research aims to determine the effectiveness of practicing adapted physical and sports activities within semi-pedagogical centers as a treatment for an autistic child. This is according to the opinions of specialists on the one hand and the view of parents according to popular beliefs on the other hand. The descriptive analytical method was used to verify the hypotheses of the study, where The original population size for the research represented: 27 autistic children, 4 specialists, 27 guardians. The sample was a survey of the study population, excluding guardians. The sample size was only 18 guardians. It was an intentional method, as the researcher conducted observation and interviews, and the research concluded that practicing adapted physical and sporting activities helped increase social interaction and acceptance by ordinary peers.